A Theoretical Essay on Interactions of SARS-CoV-2 Infection with Chronic Obesity Inflammation: an Application of Theoretical Knockouts - Giovani Marino Favero; Luis Paulo Gomes Mascarenhas; Meirielly Furmann; Felipe Leite de Oliveira; Mario Cezar Saffi Junior; Juliana Berton; Pedro Jeferson Miranda (Brazilian Archives of Biology and Technology, 2023)
Abstract Pathophysiological characteristics of obesity includes chronic inflammation. Complications in the respiratory tract are related to bodily problems, which lead to a restriction of lung function due to reduced volume, inducing an increase in respiratory work. SARS-CoV-2 has a high potential for contamination by respiratory secretions and, therefore, obesity is one of the main risk factors for complications. The relations between obesity and SARS-CoV-2 are complex, since the immunological agents that are activated by these processes are ubiquitous. It is well-known that network analysis can generate results about the dynamics of complex biological phenomena, such as signalling networks, neural networks, immunological networks, and so on. Here we propose and analysis and interpretation of the complex relationships between obesity and COVID-19 in a meta-analysis study using complex network modelling and the theoretical knockouts technique. In a complex network of this kind, vertices are considered as immunological agents and their relation as directed edges. We built two networks: one related to COVID-19 and obesity (synergy) and another only with COVID-19. In both networks, we have performed the knockout of all 52 vertices. These knockouts indicated that, besides the Infected Host Cell and COVID viral particle, IL-17; CD40, AR and AL channels; and Th17, were the most relevant agents in this complex network. Overall, our study indicated the superior role and importance of IL-17 in this context. Such result corroborates with the role of IL-17 in identification and prognosis of Acute Respiratory Discomfort Syndrome (ARDS).